Anthelmintics: From discovery to resistance II (San Diego, 2016). Issue 3 (December 2016) - Martin, Richard J.; Wolstenholme, Adrian J.; Caffrey, Conor R.
Abstract: The second scientific meeting in the series: "Anthelmintics: From Discovery to Resistance" was held in San Diego in February, 2016. The focus topics of the meeting, related to anthelmintic discovery and resistance, were novel technologies, bioinformatics, commercial interests, anthelmintic modes of action and anthelmintic resistance. Basic scientific, human and veterinary interests were addressed in oral and poster presentations. The delegates were from universities and industries in the US, Europe, Australia and New Zealand. The papers were a great representation of the field, and included the use of C. elegans for lead discovery, mechanisms of anthelmintic resistance, nematode neuropeptides, proteases, B. thuringiensis crystal protein, nicotinic receptors, emodepside, benzimidazoles, P-glycoproteins, natural products, microfluidic techniques and bioinformatics approaches. The NIH also presented NIAID-specific parasite genomic priorities and initiatives. From these papers we introduce below selected papers with a focus on anthelmintic drug screening and development. Graphical abstract: Highlights: Special Issue from the "Anthelmintics: From Discovery to Resistance II" meeting, San Diego, February 2016. Meeting themes: drug discovery, modes of action and resistance. Human and veterinary parasites covered. Academic and industrial attendees.